Adrenomedullin and the calcitonin receptor-like receptor system mRNA expressions in the rat heart and sensory ganglia in experimentally-induced long-term diabetes - Mistrova, Eliska; Wiegand, Silke; Sviglerova, Jitka; Pfeil, Uwe; Kuncova, Jitka; Slavikova, Jana; Kummer, Wolfgang; Chottova Dvorakova, Magdalena (General physiology and biophysics, 2014)
Both adrenomedullin and calcitonin gene-related peptide (CGRP) regulate vascular tone in the heart, being cardioprotective in hypoxia. Additionally, adrenomedullin exhibits antiproliferative and antiapoptotic functions in the myocardium, while CGRP exerts positive chronotropic effect. Their actions are mediated through the specific G protein-coupled receptor, CRLR, whose ligand affinity is determined by receptor activity modifying proteins RAMP1-3. CGRP binds to the complex formed by CRLR/RAMP1, whereas CRLR/RAMP2 and CRLR/RAMP3 serve as receptors for adrenomedullin. Here, we quantified expression of this signaling system in the rat heart and supplying sensory ganglia (dorsal root ganglia T1-T4 and vagal nodose ganglia) in streptozotocin-induced diabetes. In the course of diabetes, an increase of CRLR mRNA was noticed in the right ventricle 8 weeks and of RAMP3 mRNA in the left ventricle and right atrium 26 weeks after induction of diabetes. Relative expressions of other tested genes were not significantly altered. In the nodose vagal supplying specific cardiac afferents, but not in dorsal root ganglia which provide cardiac pain fibres, a small upregulation of CGRP expression was detected. In summary, the shifts observed in diabetes may favour a trend of a pronounced adrenomedullin signaling. These observations may provide a new possible therapeutic strategy for diabetic cardiomyopathy.
Keywords: adrenomedulin; signální transdukce; Signal Transduction; Diabetes Mellitus, Experimental; messenger RNA; regulace genové exprese; experimentální diabetes mellitus; protein podobný kalcitoninovému receptoru; Female; krysa rodu Rattus; zvířata; potkani Wistar; senzorická ganglia; RNA, Messenger; ženské pohlaví; Gene Expression Regulation; Rats, Wistar; Adrenomedullin; Rats; myokard; Animals; Myocardium; Ganglia, Sensory; Calcitonin Receptor-Like Protein